2021
DOI: 10.47836/pjst.29.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Public Tendering Practices, Issues and Directions - A Case of Pakistan Construction Sector

Abstract: Outdated tendering system is a significant obstacle in the momentum of public sector development in Pakistan. This study aims to examine various undiscovered part of public tendering through a detailed survey from key professionals, experts, and decision-makers of public projects. Furthermore, research covers the present status of public tendering in Pakistan and provides recommendations as per experts’ opinion. This paper exhaustively highlights how the classical customs of the public tendering in Pakistan co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…and countries in other regions like Kenya, Ghana, Zimbabwe etc.) that are experiencing similar difficulties in their PPP (mentioned in Gyawali et al, 2018; Gunawardana et al, 2021; Khoso et al, 2021; Komakech, 2016; Mahmood, 2016; Naude & Dzuke, 2017; Ogunsanya et al, 2019) can adopt the same methodology and further extend this research to test the improvements mentioned in this research to explore the applicability under different PPSs in respective countries.…”
Section: Discussionmentioning
confidence: 97%
“…and countries in other regions like Kenya, Ghana, Zimbabwe etc.) that are experiencing similar difficulties in their PPP (mentioned in Gyawali et al, 2018; Gunawardana et al, 2021; Khoso et al, 2021; Komakech, 2016; Mahmood, 2016; Naude & Dzuke, 2017; Ogunsanya et al, 2019) can adopt the same methodology and further extend this research to test the improvements mentioned in this research to explore the applicability under different PPSs in respective countries.…”
Section: Discussionmentioning
confidence: 97%
“…The contractor was satisfied that the quality of tender documents had been consistent. By contrast, both the client and the consultant agreed that the quality of tender documents is an ongoing issue (Khoso 2021). During the study it was revealed that tendering practice is influenced by the relationship between stakeholders or the unbalanced access to information rather than the accuracy and analysis of tender documentations (Whang 2022, Cole 2013.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The alpha (α) value ranges from 0 to 1, with a value closer to 1 indicates a more reliable outcome. The test results were verified according to (Khoso et al, 2021;Phogat & Gupta, 2019). According to which, alpha (α) greater than 0.70 is considered acceptable for a survey kind of research.…”
Section: Analysis Proceduresmentioning
confidence: 99%